Analyzing trends in APEC using data analytics - Raymond Freth A. Lagria; Brenda A. Quismorio (Philippine Institute for Development Studies (PIDS), 2022)
This paper shows that advanced analytics and traditional statistical techniques on available unstructured and structured data can be utilized to understand the themes put forward in APEC's yearly meetings and how member economies have supported these topics through the conduct of APEC projects. The application of text mining algorithms, such as topic modeling on the proceedings of APEC-level annual meetings, namely, APEC Economic Leaders' Meeting (AELM), APEC Annual Ministerial Meeting (AMM), and Senior Officials' Meeting (SOM), generated themes from the text which insight have been discussed. The topic models generated broad themes from AELM+AMM documents and more specific from SOM documents. These generated themes tended to be in the discussion for an average of three consecutive years. The theme observed to be in discussion in the longest (i.e., five consecutive years) was youth and globalization. These generated themes were found to be consistent with the actions APEC has pursued in the past years. [...]
Keywords: 330; Text Mining; Topic Modeling; APEC Meetings; APEC Topics; APEC Projects